Caesarean Section Rates and Activity-Based Funding in Northern Norway: A Model-Based Study Using the World Health Organization's Recommendation - Jan Norum; Tove Elisabeth Svee (Hindawi Limited, 2018)
Objective. Caesarean section (CS) rates vary significantly worldwide. The World Health Organization (WHO) has recommended a maximum CS rate of 15%. Norwegian hospitals are paid per CS (activity-based funding), employing the diagnosis-related group (DRG) system. We aimed to document how financial incentives can be affected by reduced CS rates, according to the WHO's recommendation. Methods. We employed a model-based analysis and included the 2016 data from the Norwegian Patient Registry (NPR) and the Medical Birth Registry of Norway (MBRN). The vaginal birth rate and CS rates of each hospital trust in Northern Norway were analyzed. Results. There were 4,860 deliveries and a 17.5% CS rate (range 13.9-20.3%). The total funding of the deliveries was €16,351,335 (CS: €6,389,323; vaginal births: €9,962,012). The CS rate varied significantly and was lower in the southern region (P<0.002). Consequently, the introduction of a cutoff at a 15% CS rate would gain the two southern hospital trusts by a budget increase of 0.2%. The two northern ones would experience 6.4% less resources. A total of €644,655 could be allocated to further quality and safety initiatives in obstetrics. Conclusion. The economic consequences of the model-based financial incentive were low, but probably sufficient to get the necessary attention and influence on the CS rate. Recommendations. A financial incentive for the reduction of CS rates should be tested as a supplement to other instruments.